Impactos da degradação do solo em rede de interações formiga-diásporo em uma área de Cerrado - Coelho, Paula Grandi Leão (2020)
Degradation of ecosystems leads to changes in the structure of biological communities through the replacement and loss of species. These changes can alter ecosystem functions performed by distinct species that perform different ecological functions. Ants play an important ecological role, such as diaspores dispersion and they can be used as models to understand how anthropic impacts alter ecosystem functions and services. Network analyzes of plant-animal interactions contain valuable biological information to assess anthropogenic impacts on biological interactions, as they help to understand patterns of species interactions and functioning across environments. This study aimed to: i) evaluate the impact of soil degradation on the richness of species that interacted with diaspores, time and distance of diaspores removal; ii) evaluate the impact of soil degradation on the rate of diaspores removal; iii) evaluate if the structure of ant-diaspores networks vary between degraded areas and reference areas (frequency of ant-diaspore interactions, specialization, modularity and robustness); iv) evaluate the effectiveness of removing diaspores between areas. The study area, inserted in the Cerrado biome, suffered severe degradation due to soil removal. The experiment was developed in three degraded savanna areas and three reference areas, in order to verify the impact effect on interactions. Through focal observations, we sampled the species of ants that interacted with the diaspore, frequency of ant-diaspore interactions, distance and time of removal. To assess the removal rate, we measured the percentage of artificial diaspores removed after 24 hours of exposure at four points located in the degraded area and in four points at reference areas. With ant-diaspore interactions, we set up interaction networks for different areas and evaluated the effects of habitat changes on the interaction structure and the effectiveness of diaspore removal. We observed that the removal time were significantly higher in the reference area. However, the richness of species that interacted with the diaspores, as well as the removal rate and distance of removal, did not differ between areas. We also observed that in the disturbed area the structure of the interaction network is altered, having a lower frequency of interaction and composition by potentially dispersing species that are more effective in removing diaspores. We conclude that the interactions between ants and diaspores are interesting models for assessing anthropogenic impacts on ecosystem functions and services. In addition, ants act as effective secondary dispersers as an auxiliary tool for environmental restoration.